2017
DOI: 10.18632/oncotarget.16857
|View full text |Cite
|
Sign up to set email alerts
|

IER5 as a promising predictive marker promotes irradiation-induced apoptosis in cervical cancer tissues from patients undergoing chemoradiotherapy

Abstract: PurposeTo define the role of immediate-early 5 (IER5) gene as a promising biomarker in predicting the radiosensitivity and prognosis of cervical cancer patients receiving cisplatin-based concurrent chemoradiotherapy (DDP-CCRT).ResultsOur investigations found that IER5 level was markedly elevated in cervical cancer patients after being treated with irradiation, which indicated IER5 was closely dose induced. By contrast, the correlation between IER5 and radiosensitivity cannot be confirmed by the present study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Moreover, the expression level of PAF1 in both the Siha and Hela cells was decreased after radiation Studies in recent years have suggested that PAF1 is a pivotal transcription factor for certain "induced" genes [32]. Since the results from our earlier studies demonstrated that the expression of IER5 could be induced in radiation-exposed CC cells [12], in this study, we correlated PAF1 with IER5 in both CC tissue and different cell lines. First, the localization analysis of IER5 in cells from CC tissue revealed anti-correlated expression with PAF1.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, the expression level of PAF1 in both the Siha and Hela cells was decreased after radiation Studies in recent years have suggested that PAF1 is a pivotal transcription factor for certain "induced" genes [32]. Since the results from our earlier studies demonstrated that the expression of IER5 could be induced in radiation-exposed CC cells [12], in this study, we correlated PAF1 with IER5 in both CC tissue and different cell lines. First, the localization analysis of IER5 in cells from CC tissue revealed anti-correlated expression with PAF1.…”
Section: Discussionmentioning
confidence: 85%
“…Efforts have been made to identify genes responsible for controlling radiosensitivity in CC cells, which involve DNA damage repair [3,4], cell cycle monitoring [5,6], apoptosis [7,8], signal transduction [9,10], and the tumor microenvironment [11]. Results from our previous study showed that the expression of immediate-early response 5 (IER5) was upregulated in CC tissues after treatment with radiotherapy [12]. IER5, as a member of the early-response protein family, can be stimulated by sleep deprivation, hormones, radiation, drugs, etc.…”
mentioning
confidence: 99%
“…The results of the present study indicated one CpG island and several potential methylation sites. Liu et al (10) and Shi et al (11) demonstrated that radiation could upregulate the expression levels of IER5 . Therefore, we proposed that the methylation levels of the wild type IER5 gene may be low, but could notably increase following radiation exposure, inducing its expression (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al (7), Kawabata et al (8) and Nakamura et al (9), also observed the cell cycle regulation by IER5 during the progression of different diseases. Our research group has demonstrated that radiation can induce upregulation of IER5 in tumor cells (10,11) and this process can modulate the transcription of cell division cycle ( CDC ) 25B by competitively binding to the CDC25B promoter (12). Additionally, we reported that decreased IER5 expression could increase the population of cancer cells in the G 2 /M phase of the cell cycle (13,14), and that binding of a novel transcription factor and GC binding factor (GCF) to the IER5 promoter could act as a negative regulator of IER5 transcriptional activity (15).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of genes are involved in the development of radioresistance in CC cells, such as thyroid hormone receptor interactor 4, hypoxia inducible factor‐1α and so on . Conversely, immediate‐early gene 5 can enhance the radiosensitivity of tumor cells and induce apoptosis of CC cells . Coactivator‐associated arginine methyltransferase 1 (CARM1) is a protein with arginine‐specific histone methyltransferase activity and is a coactivator of many nuclear receptors and transcription factors .…”
Section: Introductionmentioning
confidence: 99%